2001
DOI: 10.1007/s004380000412
|View full text |Cite
|
Sign up to set email alerts
|

The tetratricopeptide repeat domains of human, tobacco, and nematode PEX5 proteins are functionally interchangeable with the analogous native domain for peroxisomal import of PTS1-terminated proteins in yeast

Abstract: In the yeast Saccharomyces cerevisiae, beta-oxidation of fatty acids is compartmentalised in peroxisomes. Most yeast peroxisomal matrix proteins contain a type 1C-terminal peroxisomal targeting signal (PTS1) consisting of the tripeptide SKL or a conservative variant thereof. PTS1-terminated proteins are imported by Pex5p, which interacts with the targeting signal via a tetratricopeptide repeat (TPR) domain. Yeast cells devoid of Pex5p are unable to import PTS1-containing proteins and cannot degrade fatty acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Tetrapeptide repeat (TPR) motifs are protein–protein interaction modules that are present many functionally diverse proteins and contribute to specific interactions with chaperone proteins [ 54 , 55 ]. Previous studies found that AtCHIP (AT3G07370) interacts with molecular chaperones such as Hsc70 through its TPRs and may therefore regulate the switch from molecular chaperon-assisted protein folding to proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Tetrapeptide repeat (TPR) motifs are protein–protein interaction modules that are present many functionally diverse proteins and contribute to specific interactions with chaperone proteins [ 54 , 55 ]. Previous studies found that AtCHIP (AT3G07370) interacts with molecular chaperones such as Hsc70 through its TPRs and may therefore regulate the switch from molecular chaperon-assisted protein folding to proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…PEROXIN ( PEX ) genes are responsible for peroxisome biogenesis, including protein transport from yeast, mammalian cultured cells, and plants ( 13 , 14 , 15 , 16 , 17 , 18 , 19 ). PEX5 and PEX7 function as the PTS1 and PTS2 receptors, respectively, in yeast ( 20 , 21 ), mammals ( 22 , 23 ), and plants ( 24 , 25 , 26 , 27 , 28 , 29 , 30 ). These receptors recognize PTS1 or PTS2, bind to them in the cytosol, and direct them to the transport machinery consisting of PEX14 ( 31 ), PEX12 ( 16 , 32 ), PEX13 ( 16 , 32 ), and other unidentified factors on the peroxisomal membrane.…”
mentioning
confidence: 99%